2000
DOI: 10.21273/hortsci.35.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination of Selected Provenances of Atlantic White-Cedar as Influenced by Stratification, Temperature, and Light

Abstract: Seeds of six provenances (Escambia Co., Ala.; Santa Rosa Co., Fla.; Wayne Co., N.C.; Burlington Co., N.J.; New London Co., Conn.; and Barnstable Co., Mass.) of Atlantic white-cedar [Chamaecyparis thyoides (L.) B.S.P.] were stratified (moist-prechilled) for 0, 30, 60, or 90 days at 4 °C. Following stratification, seeds were germinated at 25 °C or an 8/16-hour thermoperiod of 30/20 °C with daily photoperiods at each temperature of 0 (total darkness), 1, or 24 hours. The germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Contrarily to the rest of the populations in which no light effect was observed, significantly higher germination rates were achieved in darkness in seeds from Grazalema. A differential light effect depending on the seed origin was also found in Chamaecyparis thyoides [ 35 ], Pinus canariensis and Pinus halepensis [ 19 ]. Therefore, although in conifer seeds light sensitivity appears to be determined by the species [ 21 ], intraspecific variations can also be expected, especially in species with a wide geographical distribution [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily to the rest of the populations in which no light effect was observed, significantly higher germination rates were achieved in darkness in seeds from Grazalema. A differential light effect depending on the seed origin was also found in Chamaecyparis thyoides [ 35 ], Pinus canariensis and Pinus halepensis [ 19 ]. Therefore, although in conifer seeds light sensitivity appears to be determined by the species [ 21 ], intraspecific variations can also be expected, especially in species with a wide geographical distribution [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interpopulation variability in germination is considered a general trend in conifer species [ 19 ]. Thus, intraspecific differences have been reported in Abies guatemalensis [ 36 ], Abies koreana [ 37 ], Pinus nigra [ 19 , 22 ], Pinus pinea , Pinus pinaster [ 19 ], Chamaecyparis thyoides [ 35 ], Pinus flexilis and Picea engelmannii [ 26 ]. Differences in germination capacity among seeds from different provenances have been attributed to genetic variations [ 25 , 38 ], although an important influence of the maternal environment has also been pointed out [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to its longevity and early fruiting that appears from 15-20 years, natural regeneration or seedling cycle of the Atlas cedar is subject to strict environmental constraints; determined by the requirements of the species vis-a-vis water, soil and cold (Toth, 1980;Illoul et al, 2004;krouchi et al, 2004). Hinesley et al (1994) and Jull and Blazich (2000) reported the inability of Atlas cedar to compete on dry sites. Drought is an important factor in seedling mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Under controlled conditions, Jull et al (1999) found different temperature optima for seedlings of six provenances, ranging from 21 8C for Massachusetts seedlings to 25 8C for Alabama seedlings. In another study, Jull and Blazich (2000) showed that stratification requirements for seed germination varied among provenances. The available data, though based on a small number of populations, provide some evidence of adaptively relevant geographic variation.…”
Section: Introductionmentioning
confidence: 99%